Group childcare has a positive impact on child development from the Japan Environment and Children’s Study - Keita Kanamori; Tomohisa Suzuki; Chiharu Ota; The Japan Environment and Children’s Study Group (Scientific Reports)
Abstract This study aimed to investigate the impact of early group childcare on child development using data from the Japan Environment and Children’s Study. This prospective cohort study enrolled participants between January 2011 and March 2014. The Ages and Stages Questionnaires (ASQ)-3 was used to obtain data regarding group childcare and other factors. The participants were divided into two groups: the early childcare group (exposed group) and the non-early childcare group (control group). The ASQ-3 scores in all five domains, i.e., communication, gross motor skills, fine motor skills, problem-solving, and personal-social skills, were compared. A total of 39,894 participants were included in this study. The exposed and control groups comprised 13,674 and 26,220 participants, respectively. The number of participants with the ASQ-3 values below the cut-off value did not differ significantly between the two groups in any of the five domains at six months of age. However, the number of participants with the ASQ-3 values below the cut-off values was significantly lower in the exposed group for all five domains at three years of age. The difference between the two groups, especially in terms of communication and personal-social skills, increased with age.